Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Hasil Belajar IPA pada Siswa Kelas V - Sulistiyani, Betti Dwi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study purpose to improve learning outcomes in Science Theme fifth Sub-theme first about the life cycle of animals in grade V students of SD Negeri 1 Kemasan , Polokarto District, 2019/2020 academic year. This study uses a Classroom Action Research (CAR) model which is carried out in 2 cycles. Each cycle consists of four stage of planning, implementation, observation/evaluation, and reflection. The Data collection in this reseacrh is by doing observation and test method. The Data was analyzed with statistic descriptive analysis method. The results showed that there was an increase in student learning outcomes using the Project Based Learning. In the pre-cycle stage of 23 students who achieved learning completeness 7 students (30,43%). Then in the first cycle of learning completeness reached 16 students (69,57%) and in the second cycle there was an increase to 23 students (91.30%). So the conclusion of this study shows that learning with the Project based Learning model improves science learning outcomes about the life cycle of animals of grade fifth students of SD Negeri Kemasan 01, Polokarto District, semester I of the 2019/2020 school year.